Cursed - Armentrout, Jennifer L. (Spencer Hill Press, 2012)
After a car accident, high school senior Ember McWilliams has the gift of touch that makes everything die. She meets Hayden Cromwell who claims her curse is a gift and can help her control it, but whose stepfather she may not be able to trust.